Teacher competencies and their role in promoting pre-service teachers’ professional growth - Hamiddin Hamiddin; Febti Ismiatun; Yuli Ismi Nahdiyati Ilmi; Helmi Wicaksono (Journal of Research on English and Language Learning (J-REaLL), 2026)
This study examined how teacher support, through mentorship, instructional guidance, and relational encouragement, shapes the professional development of pre-service teachers in Indonesian teacher education programs, particularly in influencing their perceptions, readiness, and development of core teaching competencies. A descriptive quantitative design was employed, involving 85 participants who completed a structured questionnaire measuring four key domains of teacher competence: personality, pedagogical, social, and professional. Data were analysed using SPSS, incorporating reliability testing, classical assumption tests, and path analysis to examine the hypothesized directional relationships among these competencies, where personality, pedagogical, and social competencies were modeled as predictors of professional competence. The results indicated that personality, pedagogical, and social competencies significantly and directly influenced professional competence as the outcome variable representing pre-service teachers’ preparedness for teaching. Among these, personality competence had the strongest individual impact. These findings highlighted the multifaceted nature of the relationship between teacher educators and pre-service teachers, both formal and informal, which played a critical role in fostering professional identity and instructional confidence by strengthening foundational competencies. By focusing on pre-service teachers’ perspectives, this study addressed an essential gap in the literature concerning how competency domains interact to form overall professional competence and provided evidence-based insights for enhancing teacher education programs. Ultimately, the study underscored the need for holistic and responsive teacher training models that integrated interpersonal, ethical, and instructional dimensions aligned with the competency pathways identified in this study to better equip future educators.